PERSEPSI DIRI MENGENAI KECEMASAN PADA MAHASISWA YANG MENGALAMI TEKANAN AKADEMIK TINGGI - Calista Anastasya; Astuti Darmiyanti (TABYIN: JURNAL PENDIDIKAN ISLAM, 2026)
This research aims to explore students' self-perception of the anxiety experienced due to high academic pressure. Academic anxiety is a common psychological phenomenon among students, especially when facing the demands of assignments, exams, and academic expectations. Using a qualitative approach and in-depth interviews with 15 students from various study programs, this article reveals how students interpret pressure and how their perceptions affect their levels of anxiety. The findings indicate that negative self-perception increases anxiety, while positive perception contributes to psychological resilience. This article also discusses the implications for counseling guidance and campus intervention strategies.